A study on building defects pattern of government office building (Negeri Sembilan) / Siti Safura Jamaludin - Jamaludin, Siti Safura (2012)
Building defect is a phenomenon common to most buildings. The variations arise in expressions of deliberate or rapid rate of defects occur. CIB 1993 interpreted defect as non-conformity with standard or shortfall in performance while ISO 15686-1:2000 define crack known as a fault or deviation from the intended performance of the building or its part. Repetition form of defects often occurs in the building such as Crack, Dampness, Fungus Stains and Harmful growth, Corrosion and Insect or animal attack. The research method by carried out interviews session and observation from building condition survey to gain Building Defect Pattern data and details about Category of Building Defect Failure. The data collection and analysis has shown the Building Defects Pattern and Category of Building Defect Failure that will be a reference to Government bodies before construct any office building that could reduce cost and risk of performance failure.